Bestowers of Books and Knowledge: On the Collection Bequeathed by Jean-Pierre and Colette Diény to the National Academic Library of Strasbourg - Bizais-Lillig, Marie (Journal of the European Association for Chinese Studies, 2025)
In 2015, a collection of books on Asia, and China more specifically, was donated to the Bibliothèque Nationale et Universitaire de Strasbourg in France. The donors were Jean-Pierre and Colette Diény. The collection is very large, it reflects some of the characteristics of the two sinologists’ research, and it opens up new possibilities for education and research in the field of sinology. 2015年，法國史特拉斯堡國立學術圖書館獲贈一批關於亞洲，尤其是中國研究的重要書籍。這批藏書由桀溺（Jean-Pierre Diény）和科萊特．帕特（Colette Diény）夫婦捐贈，規模宏大，不僅體現了兩位漢學家在學術研究中的獨特視角，還為亞爾薩斯的漢學教育與研究開闢了新的領域。